2015
DOI: 10.18632/oncotarget.6030
|View full text |Cite|
|
Sign up to set email alerts
|

5-Fluorouracil-induced RNA stress engages a TRAIL-DISC-dependent apoptosis axis facilitated by p53

Abstract: Despite recent advances in targeted therapeutics, administration of 5-fluorouracil (5-FU) remains a common clinical strategy for post-surgical treatment of solid tumors. Although it has been proposed that RNA metabolism is disturbed by 5-FU treatment, the key cytotoxic response is believed to be enzymatic inhibition of thymidylate synthase resulting in nucleotide pool disproportions. An operating p53 tumor suppressor signaling network is in many cases essential for the efficiency of chemotherapy, and malfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The determination of dynamic radical changes in cellular microenvironment with non-invasive approaches is an essential mean for assessing the effectiveness of anticancer agents on cancer treatment [45][46][47][48]. As mentioned above, 5-FU's chemotherapeutic properties are attributed to thymidylate synthase (TS) activity inhibition, to mitochondrial ROS generation and the caspases cascade activation [49]. Our findings demonstrate that 5-FU differentially affects superoxide production and caspase-3 activation when applied in cytotoxic concentrations against HeLa cells.…”
Section: Discussionmentioning
confidence: 54%
“…The determination of dynamic radical changes in cellular microenvironment with non-invasive approaches is an essential mean for assessing the effectiveness of anticancer agents on cancer treatment [45][46][47][48]. As mentioned above, 5-FU's chemotherapeutic properties are attributed to thymidylate synthase (TS) activity inhibition, to mitochondrial ROS generation and the caspases cascade activation [49]. Our findings demonstrate that 5-FU differentially affects superoxide production and caspase-3 activation when applied in cytotoxic concentrations against HeLa cells.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, several studies have observed that the cytotoxicity of 5-FU is more dependent on its incorporation into RNA than its inhibition of TS, diminishing its effect on DNA (21,(34)(35)(36)(37). In addition, activation of p53 following 5-FU exposure has been identified as working through RNA mechanisms (43,44). Because UDG recognizes only DNA lesions, it is not surprising that depletion of UDG does not significantly alter cellular responses to agents that primarily affect RNA function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, retinoids and interferons have been demonstrated to stimulate cell death by means of TRAIL [ 12 ]. Similarly, our recent work emphasized that 5-Fluorouracil (5-FU) can induce apoptosis following the activation of DRs via an intracellular TRAIL-stimulated mechanism [ 13 ]. In the present study, initiated with the aim to analyze crosstalk between apoptosis and autophagy, we demonstrate that cell death generated by 5-FU requires cytoplasmic transport of DR5, which in turn seems to be tightly associated with free cholesterol.…”
Section: Introductionmentioning
confidence: 99%